Strategi Pengembangan Bisnis Jasa Layanan Logistik J&T Express Dengan Pendekatan Business Model Canvas (BMC) - Prasetya, Syarief Gerald; Maria, Maya (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study was aimed to explore the logistics service business strategy of J&T Express using the Business Model Canvas (BMC). The research locus was chosen at J&T Express as an innovative logistics service company. This research was compiled based on a qualitative descriptive method. The time of the study was conducted in April 2022, located in Bogor City and the analytical technique used was Miles and Huberman's qualitative interactive. Based on the use of nine dimensions of BMC, with the possibility of making managerial contributions that are included in tactical and strategic approaches, the J&T Express business model approach is in accordance with BMC. The contribution of this research emphasizes that the canvas business model (BMC) can be used as a role model in a comprehensive logistics service business development strategy.